Techniques for Measuring Aerosols using the Central Laser Facility at the Pierre Auger Observatory - Abreu, P.; Aglietta, M.; Ahlers, M.; Ahn, E. J.; Albuquerque, I. F. M.; Allekotte, Ingomar; Almela, Daniel Alejandro; Asorey, Hernán Gonzalo; Bertou, Xavier Pierre Louis; Dasso, Sergio Ricardo; de la Vega, Gonzalo Andrés; Dova, Maria Teresa; et al. (IOP Publishing, 2013)
Fil: Abreu, P.. Universidade Técnica de Lisboa; Portugal